First Tunisian cluster admissions of critically ill patients with multisystem inflammatory syndrome in children (MIS-C) - aida borgi (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Multisystem inflammatory syndrome in children (MIS-C) is a new serious emerging disease that is temporally related to previous exposure to coronavirus infection disease (COVID-19).